Recent Developments in Gravity : Proceedings of the Hellenic Relativity Conference. - Kokkotas, Kostas D. (World Scientific Publishing Company, 2003)
This book contains the proceedings of the 10th Hellenic Relativity Conference, held in Greece in 2002. It includes several plenary lectures given by leading experts on brane-world cosmology, radiative space-times, detection of gravitational waves, gamma-ray bursts and quantum gravity. There are a large number of contributed papers, organized into three broad subject areas: cosmology and brane gravity, mathematical relativity and astrophysical relativity, and the detection of gravitational waves. Contents: Radiative Fields in Spacetimes with Minkowski and de Sitter Asymptotics (J Bicák); Gravit.